Expression of Vitamin D Receptor and Vitamin D Receptor Gene Polymorphisms (BsmI, FokI, and TaqI) in Patients with Pterygium - Bilak,Şemsettin (2021)
ABSTRACT Purpose: This study aimed to determine the role of vitamin D receptor in the pathogenesis of pterygium. The vitamin D receptor eexpression levels in pterygium tissue, blood vitamin D levels, and frequency of selected vitamin D receptor gene polymorphisms (BsmI, FokI, and TaqI) were compared between patients with pterygium and healthy participants. Methods: The study included patients with pterygiumeee (n=50) and healthy volunteers (n=50). The serum vitamin D levels were measured for both groups. Immunohistochemical staining for vitamin D receptor ewas performed on sections obtained from the pterygium and adjacent healthy conjunctival tissues of the same individuals. The genomic existence of vitamin D receptor epolymorphisms (BsmI, FokI, and TaqI) were analyzed in DNA obtained from venous blood of participants using polymerase chain reaction and restriction fragment length polymorphism methods. Results: There was no difference found between the serum vitamin D levels of patients with pterygium and healthy controls. However, tissue expression of vitamin D receptor was higher in the pterygium endothelial cells of micro-vessels (p=0.002), subepithelial stromal (p=0.04), and intravascular inflammatory cells (p=0.0001), in comparison with the adjacent healthy conjunctival tissue. Moreover, while the BBtt haplotype was 2-fold higher, the bbTt haplotype was 2.5-fold lower, and the BbTT haplotype was 2.25-fold lower in the control group than in the pterygium group (p<0.001). Conclusions: Vitamin D serum levels did not differ between the healthy and pterygium groups. Vitamin D receptor expression was increased in the pterygium tissue versus the adjacent healthy tissue. However, vitamin D receptor polymorphism analysis in patients with pterygium did not reveal any significant difference in BsmI, FokI, or TaqI polymorphisms in comparison with the healthy volunteers.